Island trilogy - Korman, Gordon (New York : Scholastic, 2005)
A collection of three books about a group of kids who are shipwrecked on an island with strangers and they just want to survive.
Shipwreck -- Survival -- Escape.
Three books in one.
Keywords: Shipwrecks -- Juvenile fiction; Shipwreck victims -- Juvenile fiction; Shipwreck survival -- Juvenile fiction